Meningkatkan Hasil Belajar Siswa Kelas Bawah Pada Pembelajaran Matematika Dengan Media Dakon - Pinahayu, Pinasti; Prayogo, Ahmad Singgih; Hajron, Kun Hisnan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this study is to determine the influence of the use of dakon media inimproving numeracy skills in lower grade elementary school students. This researchuses pre-experimental research method with one group pretest and posttest researchdesign design. The subjects of this study were as many as 10 grade 1 elementaryschool students consisting of various schools. The research is divided into two cycles,namely before and after being given special treatment. The mean test result beforetreatment is 41 and the posttest test result gets 79 which results in the meandifference between pretest and posttest which is 38. Where there is a mean increasefrom the pretestt to the posttest. From the results of the study students showed anincrease of pretest which only showed that as many as 90% of students wereincomplete and only 10% of students completed. The student learning results in theposttest test showed an increase of 20% of students were incomplete and 80% ofstudents completed.